Faktor Sosiodemografis dan Partisipasi Wanita Bekerja di Sektor Informal: Studi Komparatif Wilayah Perkotaan dan Perdesaan Indonesia - Al Iffah, Nisa; Bachtiar, Nasri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study aims to analyze the influence of sociodemographic characteristics on the probability of women's participation in the informal sector, using logistic regression on 115,622 observations from the August 2023 National Labor Force Survey (SAKERNAS). The analysis reveals that low educational attainment is the most significant determinant driving women's involvement, particularly in rural areas. In addition, short working hours, marital status, and work experience also increase participation, while living in urban areas, having a larger household size, and the use of technology significantly reduce the likelihood of involvement. These findings underscore the importance of region-based policies that expand access to education, job training, and digital literacy, thereby strengthening women's position in the informal sector.